Toxicities of Six Phenolic Derivatives and Six Heavy Metals to the Fresh Water Luminescent Bacterium Vibrio qinghaiensis sp.-Q67 - Li, Y.H.; Mo, L.Y.; Zhang, X.H.; Liu, H.L.; Liu, J.; Liu, H.Y. (Asian Journal of Chemistry, 2014)
Six phenolic derivatives (methyl phenol, 2-nitrophenol, 4-nitrophenol, 2-chlorophenol, 2,4-dichloro-phenol, phenol) and six heavy metals (Cu, Ni, Hg, Cd, Cr, Hg) were selected to investigate the joint toxicity of them, as well as their mixtures to Vibrio qinghaiensis sp.-Q67. The joint toxicity of twelve uniform design concentration ratio (UDCR) mixtures could be overestimated by the dose addition or by the independent action model within 95 % confidence intervals. All dose-response relationships could be effectively described by the two-parameters i.e., Weibull or Logit function with correlation coefficient (R) greater than 0.99. Results indicate that when the total effects of mixtures were below 30 %, the mixture toxicity interactions were antagonistic actions, except for one uniform design ray of Mix-U1. With the increasing of the concentration, the effect of toxicity become opposite, for the mixtures are not in the same toxicity system. Value of b is large interval in the 3.90-10.98 range.